The influence of gender and educational attainment differences on international migrants' occupational status in OECD countries - Main Al-Dalahmeh; Imran Sarihasan; Krisztina Dajnoki (Economies, 2021)
The purpose of the study is to show two essential elements of the occupational status of international migrants in OECD countries. The study extends the current research by focusing on how the educational attainment of international migrants and the gender dimension affect migrants' occupational status. To achieve the aim of the study, a quantitative research approach was followed. Ordinary least square regression analysis was used to emphasize the relationship between educational attainment and gender differences, and occupational status. The databases were taken from the OECD DIOC 2015/2016. It has been found that high-level educational attainment matches with representative vacancies, and female migrants tend to have those occupations more than male migrants in OECD countries. On the other hand, the study's limitations included a lack of data on testing the exact occupational status of migrants in OECD countries, as well as educational attainment levels that were not specifically divided into each level of education in the databases.
Keywords: 330; education; gender differences; labour sector; migration; occupational status; SDGs